Improving Student Competence in The Era of The Industrial Revolution 4.0 Through The MBKM Program - Syahril Syahril; Karunia Puji Hastuti; Desy Arisanty; Ersis Warmansyah Abbas (Social Studies Conference Proceedings, 2022)
Merdeka Belajar-Kampus Merdeka is a policy of the Minister of Education and Culture, which aims to encourage students to master various sciences that are useful for entering the world of work. Kampus Merdeka allows students to choose the courses they will take. Through Merdeka Belajar – Kampus Merdeka, students have the opportunity to take 1 (one) semester or the equivalent of 20 (twenty) credits of studying outside the study program at the same university; and a maximum of 2 (two) semesters or equivalent to 40 (forty) credits of studying in the same study program at different universities, learning in different study programs at different universities; and/or out-of-College learning. Learning in the Merdeka Campus provides challenges and opportunities for the development of creativity, capacity, personality, and student needs, as well as developing independence in seeking and finding knowledge through reality and field dynamics such as ability requirements, real problems, social interaction, collaboration, self-management, performance demands, targets, and achievements.